Genome Sequence of Klebsiella quasipneumoniae subsp. similipneumoniae MB373, an Effective Bioremediator - Aslam, Fozia (Genome Announc, 2016)
Klebsiella quasipneumoniae subsp. similipneumoniae MB373 was isolated from effluent of the Hattar Industrial Estate, Haripur, Pakistan. K. quasipneumoniae subsp. similipneumoniae has few cultivated/characterized members so far. Whole-genome sequencing revealed its potential for metal and toxin resistance, which further elucidated various enzymatic processes for the degradation of xenobiotics, illuminating its bioremediation applications.